2001
DOI: 10.1046/j.1440-1800.2001.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Social poetics as research and practice: living in and learning from the process of research

Abstract: This paper is both a report of research work carried out by one author of the paper with the other involved in a supervisory role, and a reflection on methodology that was an emergent property of the research process. The research question arose when professional preunderstandings about schizophrenia as a biological disturbance were bracketed as a Husserlian form of phenomenology was adopted. The initial study focused on the meanings three individuals attached to being diagnosed with a mental illness and being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Schizophrenia is described as biochemical imbalances in neurotransmitters, manifested as disruptions to thoughts, perceptions, or behaviours, yet this discounts the extent to which mental illnesses are experienced as disturbances of normal bodily feelings and functions (Rudge & Morse, 2001). Aldridge and Stevenson (2001), for example, describe a person with schizophrenia whose delusions featured a belief that her body had become severely distorted, while for other sufferers the condition may present as though the body is acting of its own accord, not under conscious control (Hensley, 2002;Usher, 2001). …”
Section: Embodimentmentioning
confidence: 99%
See 1 more Smart Citation
“…Schizophrenia is described as biochemical imbalances in neurotransmitters, manifested as disruptions to thoughts, perceptions, or behaviours, yet this discounts the extent to which mental illnesses are experienced as disturbances of normal bodily feelings and functions (Rudge & Morse, 2001). Aldridge and Stevenson (2001), for example, describe a person with schizophrenia whose delusions featured a belief that her body had become severely distorted, while for other sufferers the condition may present as though the body is acting of its own accord, not under conscious control (Hensley, 2002;Usher, 2001). …”
Section: Embodimentmentioning
confidence: 99%
“…There is a loss of self because the body no longer acts in the familiar, trusted ways. Sufferers become an "other" to the self they knew previously, an event that is both bewildering and frightening (Aldridge & Stevenson, 2001;Rudge & Morse, 2001;Usher, 2001). This is often accompanied by hopelessness and grief for the normal life that is lost, and future plans that will never materialise (Hensley, 2002;Horowitz, 2002).…”
Section: Lived Experience Of Schizophreniamentioning
confidence: 99%
“…By observing and highlighting the poetics of everyday speech within human interaction, researchers create rather than discover new understandings of human experience and interaction (Aldridge & Stevenson, 2001). The use of poetics within the data analysis and presentation of findings in this project allowed access to unexpected and hidden thoughts, feelings and meanings from a particular participant's point of view.…”
Section:  Social Poeticsmentioning
confidence: 99%
“…In 1998, a MSc student (Dee Aldridge) I was supervising decided to conduct a small‐scale research study that would describe the experience of being in schizophrenia (Aldridge 1998). A full account of the study is found in Aldridge and Stevenson (2001). She chose a phenomenological approach, appropriate to the research question.…”
Section: The Woman Who People Mistook For a Schizophrenic: A Nursing mentioning
confidence: 99%